2010
DOI: 10.1016/j.socscimed.2009.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Conflict between the work and family domains and exhaustion among vocationally active men and women

Abstract: Exhaustion is consistently found to be more prevalent in women than in men. Women suffer from job strain more often, which may constitute a partial explanation for this phenomenon, but experienced shortcomings in combining work and family demands may also contribute to ill health. The aim of this study was to investigate, and analyse by gender, how work-related and family-related factors, as well as the interface between them, i.e. work-to-family conflict (WFC) and family-to-work conflict (FWC), are related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
2
27
0
4
Order By: Relevance
“…Super et Neville (1986) travail (Canivet et al, 2010 (Emslie, Hunt, & Macintyre, 1999;Hall, 1989;Sjogren & Kristenson, 2006). (Gotlib & Cane, 1989;Massé, 1999;Massé et àl 9 1998b;Weissman, Myers, & Ross, 1988).…”
Section: Importance Et Investissement Dans Les Rôles De Vieunclassified
See 1 more Smart Citation
“…Super et Neville (1986) travail (Canivet et al, 2010 (Emslie, Hunt, & Macintyre, 1999;Hall, 1989;Sjogren & Kristenson, 2006). (Gotlib & Cane, 1989;Massé, 1999;Massé et àl 9 1998b;Weissman, Myers, & Ross, 1988).…”
Section: Importance Et Investissement Dans Les Rôles De Vieunclassified
“…À l'instar de la présente étude, d'autres auteurs (Canivet et al, 2010) (Biiltmann et al, 2002;Li-Huan et al, 2010). Cependant, en ce qui a trait à la relation entre la fatigue et le bien-être psychologique, aucun lien significatif n'est obtenu à l'aide de l'analyse acheminatoire.…”
Section: Observations Concernant Les Hypothèses De Rechercheunclassified
“…The articles were selected for their relevance and the topic of work-family balance. Several studies addressed work-family conflict and its impact on family and professional life as a discord between these two spheres [2][3][4][5][6][7][8][9]. Among these articles, we found that the subject was studied in a segmented mode, i.e., the daily lives of workers, including all spheres of their lives, and the interinfluence between these spheres, was not taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Balancing career and family can cause stress and anxiety, particularly for women (Ford, Heinen, & Langkamer, 2007). Women typically experience more exhaustion as a result of struggling to find work-life balance compared to men (Canivet et al, 2010). Women benefit when their significant, other demonstrates a willingness to assist in sharing household chores and familial obligations (Canivet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Women typically experience more exhaustion as a result of struggling to find work-life balance compared to men (Canivet et al, 2010). Women benefit when their significant, other demonstrates a willingness to assist in sharing household chores and familial obligations (Canivet et al, 2010). Though more egalitarian partnerships are becoming more popular, this balance of work and family is still more of a burden for women in the labor force than for their male counterparts (Bond et al, 2002;Presser, 1994).…”
Section: Introductionmentioning
confidence: 99%